Social Rights and Obligations: The Relationship Between Citizens and the Administration of Social Law in Poland - Cendrowicz, Dominika (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
The main purpose of this article is to present the relationship between citizens and the social law administration from the perspective of Polish legislation. It is a very important topic as nowadays many people are dependent on the administration of social law (or on the administration of provision) and, in fact, anyone of us might one day become a beneficiary of social benefits. Existence of significant social needs triggers the state's activity in shaping social policy. Therefore, it is no surprise that the legal protection of social rights is considered as essential from the citizens’ point of view. This is because citizens understand social rights in terms of public goods. Therefore, social rights and their protection are guaranteed by provisions of the international, EU and domestic laws of the democratic countries. In Poland, the existence of social rights is guaranteed by the Constitution and social benefits are manifestations of social rights' realisation guaranteed by the Constitution. However, the Polish legal system within the area of social security is still (especially in comparison with the German system) somewhat unstructured. Consequently, there are multiple laws regulating social benefits in Poland.
Keywords: administracja prawa socjalnego; prawa i obowiązki socjalne; Polska